تعدد أقوال الحافظ ابن حجر في الراوي دراسة مقارنة بين كتابيه تقريب التهذيب وفتح الباري: Multiple Commentaries from al-Hafiz Ibn Hajar in Narrators: A Comparative Study Between His Books Taqrib Tahdhib and Fath al-Bari - al-Abbadi, Ziyad Salim (Maʿālim al-Qurʾān wa al-Sunnah, 2018)
There is no doubt that Ibn Hajar is one of the notable scholars of Islam. He mastered the various field of knowledge. Thus, his reputation was well known by public and students. Among the sciences that he was outstanding in is the science of narrators. Whereby his commentary on most of the narrators of Prophet’s traditions was being found. But it has been observed that some of his commentaries on some of the narrators were contradicted in his several books. Some of them were judged as weak in a book and as trustworthy in the other. Therefore, this study tries to solve the problem by clarifying the contradiction by comparing to the other scholar’s commentaries on the narrators. A comparative study between his book Taqrib Tahdhib and Fath al-Bari thus be conducted to solve with the problem.